Gas Flow and Ablation of 122 mm Supersonic Rocket Nozzle Investigated by Conjugate Heat Transfer Analysis - Jatuporn Thongsri; Kamonwan Srathonghuam; Adulyasak Boonpan (My University, 2022)
The propellant gas flow of a supersonic rocket in inappropriate operating conditions can cause excessive ablation inside a nozzle. In this research, conjugate heat transfer analysis (CHTA), consisting of computational fluid dynamics (CFD) and finite element analysis (FEA), was applied to investigate the gas flow and ablation of a 122 mm nozzle as a case study in the transient state, based on actual operating conditions. First, the nozzle was tested in a static experiment. Then, the experimental results were employed for CHTA settings and validation. Next, after completing the CFD calculation, the results revealed that the nozzle’s gas flow, temperature, pressure, Mach number, shock, etc. were consistent with theoretical results. Finally, using the CFD results as loads, the FEA results showed the equivalent von Mises stress (σv), which was consistent with the ablation results from the experiment, as expected. The more the σv, the greater the ablation. Both σv and ablation were high near the throat and decreased further away. In addition, increasing the insulators’ thickness reduced σv, leading to ablation reduction. The research findings contribute to an understanding of ablation and the methodology of employing CHTA to improve the design of 122 mm and other nozzles with reduced ablation for higher efficacy.
Keywords: Rocket engine nozzle; Rocket (weapon); Rocket and propulsion systems research